Automatic license plate recognition system - Ong, Xue Li (2014)
Automatic License Plate Recognition (ALPR) system is a system that automatically recognizes the license plate of vehicles. It has become increasingly popular in many applications such as assisting the police in tracking lost or wanted vehicles or be used at gantries to control access to condominiums or buildings. This paper focus on detecting and recognizing Singapore license plate that have different sizes. The job is divided into two main steps: License Plate Recognition (LPR) and Plate Number Recognition (PNR). In the license plate recognition step, the job is further divided into plate segmentation and classification. In the plate number recognition step, character recognition is performed to read the plate number. For the practical implementation of our system, we employ OpenCV for computer vision tasks, Tesseract for character recognition and Qt for cross-platform enabled GUIs.